(untitled) (Latakia University Journal -Basic Sciences Series, 2022)
This work investigates the electronic and magnetic modifications induced by La³⁺ doping in the spinel ferrites MnFe₂O₄ and CoFe₂O₄ using density functional theory (DFT) as implemented in the CP2K package. The results show that La³⁺ incorporation slightly expands the lattice (≈0.6–0.7%) and narrows the band gap by about 0.2 eV due to hybridization between La 4f and Fe 3d states near the Fermi level. The structural expansion increases the Fe–O–Fe bond angle, thereby enhancing the superexchange interaction and improving the magnetic ordering. Overall, La³⁺ doping at low concentrations offers a practical route to tune the electronic and magnetic properties of ferrite oxides without compromising their structural stability, making them promising candidates for spintronic and magnetic storage applications.